Intrathoracic Goiter: (50 cases). Clinical Aspects. Diagnosis - Suiffet, Walter (Cirugía del Uruguay, 1980)
The case material for this analysis of the elements available for diagnosis in Intratho'racic Goiter (IG), consists of 50 cases. These elements are clínica! symptomatology, simple radiology, simple and computarized tomography and radioactive isotopes.